REDUPLIKASI DAN MAKNANYA DALAM NOVEL JAMAL JAMILAH KARYA BOMA KAMPAU - NFN Marnetti (Madah: Jurnal Bahasa dan Sastra, 2014)
The aim of this research is to describe the forms and the meanings of  reduplication which is found in Jamal Jamilah novel written by Boma Kampau, one of the writers came from Kampar Regency. The method used in this research is a descriptive method. The result of the research showed that there are four forms of reduplication in this novel. They are      (1) full reduplication,  (2) part reduplication, (3) affix reduplication, and (4) reduplication with the changes of phonemes. There are three kinds of meaning in reduplication, the first meaning is indicated many meanings, the second is indicated repetition, and the third is indicated the meaning of the action which is done well, cassually and leisurely.